ANALISA PEMADATAN TANAH LIAT DENGAN MESIN EXTRUDER - Darmanto, Seno (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2006)
Research is done to analyze work performance of extruder machine to compress clay for red brick. Theanalyzing work performance of extruder machine is based on dry density of clay and water content. Research is done inindustry and laboratory with doing observation and taking specimen of clay that had been given treatment in extrudermachine. And based on analyzing data it shows that dry density of clay in extruder machine is in range 1.45 gram/cm3 –1.55 gram/cm3 and water content can be range 27% -31%.